IceCube-Gen2 - The Next Generation Neutrino Observatory at the South Pole: Contributions to ICRC 2015 - Collaboration, TI-G; Aartsen, MG; Abraham, K; Ackermann, M; Adams, J; Aguilar, JA; Ahlers, M; Ahrens, M; Altmann, D; Anderson, T; Ansseau, I; Anton, G; et al. (2015)
85 pages, 52 figures, Papers submitted to the 34th International Cosmic Ray Conference, The Hague 2015, v2 has a corrected author list 85 pages, 52 figures, Papers submitted to the 34th International Cosmic Ray Conference, The Hague 2015, v2 has a corrected author list Papers submitted to the 34th International Cosmic Ray Conference (ICRC 2015, The Hague) by the IceCube-Gen2 Collaboration.